2009
DOI: 10.1177/1545968309332879
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm Perturbations in Acoustically Paced Treadmill Walking After Stroke

Abstract: In gait rehabilitation practice, the use of acoustic rhythms may be more effective when both footfalls are paced. In addition, rhythm perturbations during acoustically paced treadmill walking may not only be employed to evaluate the stability of auditory-motor synchronization but also have promising implications for evaluation and training of gait adaptations in neurorehabilitation practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 38 publications
6
88
1
1
Order By: Relevance
“…[1][2][3][6][7][8][9][10]12,18 First, we found that asymmetry in neither component was significantly correlated with mean step-length asymmetry, indicating that variations in step-length asymmetry cannot be fully explained by the components of trunk progression (TP) and forward foot placement relative to the trunk (FFP) in isolation. Second, Figure 2 clearly shows that step-length asymmetry is, by and large, the sum of asymmetries in TP and FFP.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][6][7][8][9][10]12,18 First, we found that asymmetry in neither component was significantly correlated with mean step-length asymmetry, indicating that variations in step-length asymmetry cannot be fully explained by the components of trunk progression (TP) and forward foot placement relative to the trunk (FFP) in isolation. Second, Figure 2 clearly shows that step-length asymmetry is, by and large, the sum of asymmetries in TP and FFP.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy persons are able to initiate such adjustments in response to new visual information at remarkably short latency (~120 ms) and to alter their foot placement successfully according to the environmental demands. [7][8][9] After a stroke, studies have shown that the ability to make step adjustments is often impaired, [10][11][12][13][14][15] but the exact underlying deficits and their interplay remain poorly understood. In general, step adjustments could fail either because the stepping leg is adjusted too late or because the movement itself is inadequate in some way.…”
Section: Introductionmentioning
confidence: 99%
“…It has been generally known that rhythmic auditory stimulation training and treadmill training are both effective to promote normal gait pattern through providing the repetitive and intensive stimulus for motor areas in the brain [Hesse S, 2008,Thaut MH et al, 2007.Studies on RAS training have shown that when different tempos of rhythmic stimuli were given, the faster tempo led to increase in cadence and step and decrease in GA, resulting in the positive effects on recovery of gait ability [Plotnik M et al, 2007, Arias P et al, 2008,Willems AM et al, 2006.The stability of inter limb coordination was more improved when RAS was provided on both paretic and non-paretic side, compare with non-paretic side only [Roerdink M et al, 2009].…”
Section: Discussionmentioning
confidence: 96%